2017
DOI: 10.1080/14756366.2017.1363741
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human cytochromes P450 2A6 and 2A13 by flavonoids, acetylenic thiophenes and sesquiterpene lactones from Pluchea indica and Vernonia cinerea

Abstract: The human liver cytochrome P450 (CYP) 2A6 and the respiratory CYP2A13 enzymes play role in nicotine metabolism and activation of tobacco-specific nitrosamine carcinogens. Inhibition of both enzymes could offer a strategy for smoking abstinence and decreased risks of respiratory diseases and lung cancer. In this study, activity-guided isolation identified four flavonoids 1–4 (apigenin, luteolin, chrysoeriol, quercetin) from Vernonia cinerea and Pluchea indica, four hirsutinolide-type sesquiterpene lactones 5–8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Apigenin was reported to inhibit CYP2A6 activity in the metabolism dependent inhibition assay, as well as the direct inhibition assay of CYP2A6. Boonruanga et al [31] reported similar IC 50 values in metabolism dependent and direct inhibition assays of 0.77 ± 0.16 µM and 0.90 ± 0.07 µM, respectively. Likewise, under the similar experimental conditions and 1 µM concentration of apigenin, we observed comparable values of residual CYP2A6 enzyme activity: 47 ± 7% ( p = 0.037) and 48 ± 1% ( p = 0.018).…”
Section: Resultsmentioning
confidence: 87%
“…Apigenin was reported to inhibit CYP2A6 activity in the metabolism dependent inhibition assay, as well as the direct inhibition assay of CYP2A6. Boonruanga et al [31] reported similar IC 50 values in metabolism dependent and direct inhibition assays of 0.77 ± 0.16 µM and 0.90 ± 0.07 µM, respectively. Likewise, under the similar experimental conditions and 1 µM concentration of apigenin, we observed comparable values of residual CYP2A6 enzyme activity: 47 ± 7% ( p = 0.037) and 48 ± 1% ( p = 0.018).…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies showed that P. Indica leaf extract contained acetylenic thiophenes, caffeoylquinic acid derivatives, and flavonoids including apigenin, luteolin, and quercetin [13,14,37]. Notably, quercetin inhibited ICAM-1 expression in PMA-and TNF-α-induced ECV304 human endothelial cells by inhibiting the JNK pathway [38].…”
Section: Involvement Of Ho-1 Activation In the Anti-inflammatory Effect Of Pie On Human Endothelial Cellsmentioning
confidence: 98%
“…[ 13 18 ] CYP2A13 can efficiently metabolize and activate aflatoxin B1, generate a variety of metabolites including epoxide, and then combine with DNA, RNA, protein, and other biological macromolecules in the body to form DNA, RNA, and protein adducts to cause cytotoxicity, Inflammation, DNA damage, and other toxic effects, which may cause cell malignant transformation and cause body tumors. [ 19 25 ] At present, there is no consistent conclusion on the genetic polymorphism of CYP2A13 and lung cancer susceptibility. Therefore, in this study, the meta-analysis method was used to systematically evaluate the relationship between CYP2A13 gene polymorphism and lung cancer susceptibility, in order to provide a basis for exploring clinical drug targets and cancer prevention.…”
Section: Introductionmentioning
confidence: 99%